(untitled) (Anuário Antropológico, 2023)
This article sets out to describe and develop an analysis of how the precarization of the Unified Health System (SUS) affects the processes of subjectivation of the bodies that compose it. Using data collected from ethnographic research at an Alcohol and Drug Psychosocial Care Centre (CAPS AD) located in a municipality in the interior of São Paulo state, I explore the impacts that large-scale epidemiological events have on the mental health of the affected populations, particularly the healthcare professionals who continued to pursue their professional activities under such conditions. I first demonstrate the particularity of the covid-19 pandemic through an analysis of the political contingencies that singularize the Brazilian case within the pandemic’s global context. Next, I connect macrostructuring political processes with the quotidian micropolitics of care and the affects that they mobilize. To highlight the pathways through which major changes affect individual life trajectories, I use the theoretical matrix developed by the field of the anthropology of emotions. In support of my argument, I turn to interviews and ethnographic narratives that constituted my field material during my master’s degree research, initiated and completed during the covid-19 pandemic.